Assessing The Impact of Records Managers Training on Performance of Municipalities: A case Study Of Kabale Munuciplity Kabale District. - Ninshaba, Clare (Kabale University, 2024)
The most outstanding aim of this study was assessing the impact of Records Managers Training on the performance of Municipalities. The objectives of the study were; to find out the role of Records Managers on the performance of the municipality, to find out the types or records kept in :,3bale municipality, to find out the challenges faced by Records Managers in the management of records, and to find out the possible solution to the challenges face by record managers in managing record in Kabale Municipality. The study was carried out in Kabalc municipality and data was corrected from I5 respondents including administrative staff, registry staff, and clients. Some administrators were given questionnaires and interview schedules to those who we,-c very busy and could not get enough time to answer questionnaires. The collected data was checked and analyzed. tabulated and calculated in percentages and degrees and the results obtained indicated that Records Managers play a very big role in the performance of Kabale Municipality. The major findings of the study about the role of Records Managers were. Promoting accountability, facilitating decision-making, saving time and space, and proper administration However, the respondents also indicated that there also some challenges that were being faced by Records Managers of Kabale municipality but some possible solutions were proposed. Finally, the following recommendations were advanced by the rcscn,·cher. There is a need to introduce other methods of security of records management systems such as the use of computer program packages such as database and pastel respectively for this can reduce the tow and growth of paper records, there also should be skilled personnel who have more experience and proper training in the field of records management, there also should tic on job training especially the records staff of Kabale municipality in order !' or them to keep updating themselves with current methods of managing. maintaining and preserving records. The records manager should procure other storage equipment to cater to the growing paper records.